STUDENTS’ ABILITY AND DIFFICULTIES IN CONSTRUCTING CONDITIONAL SENTENCE TYPE II AT SMAN 10 KERINCI JAMBI - Nurmalia Sari, Mike (Dharmas Education Journal (DE_Journal), 2023)
Conditional sentences Type II are an important part of communication, especially in expressing hypothetical situations. This can help students understand how to communicate more effectively, and is an important skill in language proficiency and can help identify areas that need improvement, leading to the development of better language skills. This study identifies students' difficulties in understanding and reproducing the type II conditional sentence by using grammar test and interviews. This study aims to determine students' abilities in constructing type 2 conditional sentences and the problems faced by students. The research design is descriptive. The population is all grade II students of SMAN 10 Kerinci Jambi Province and the sample is students of class XI MIPA I. The research instruments used were grammar tests and interviews. The results showed that the average ability of students to construct conditional sentences was low, with an average score of 62 (categorized C). The difficulties faced by students were confusion in the use of verb-2 and to be for the past tense, students' ignorance of irregular verbs, confusion in determining causal sentence parts in conditional sentences. Finally, sentence conditioning type 2 is difficult, but it can be learned if students practice more in constructing sentences.